Syair Syurga a devotional literary text in an early Malay printed book from Sumatra - Suryadi, (Universiti Kebangsaan Malaysia, 2009)
This paper discusses an early twentieth century Malay literature that could be called ‘sastra dakwah’ (religious proselytizing literature), in the broader category of ‘sastra Islam’ (Islamic literature). Entitled Syair Syurga, it outlines tarekat teachings about the levels of consciousness and gives a symbolic interpretation of the prayer ritual. It tells about the reward that will be gained by pious Muslims in the hereafter, where they will live happily forever in heaven. This paper provides a transliteration of the poem in the Roman alphabet, reviews its content, and provides an account of the authorship of the poem. In short, this paper examines the motif of afterlife in classical Malay literature. By examining the ‘coalition’ of religion and literature in classical Malay text like The Poem of Heaven, our understanding of local Islam in the Malay world in its historical perspective will be enhanced